Implementation Process of Product Lifecycle Management Applications in the Context of Enterprise Information Systems: Analysis of a Defense Industry Organisation - Yüksel, Gökçe; Çakmak, Tolga (Information World, 2024)
This study investigates the factors to be considered during the implementation of product lifecycle management practices, which is one of the approaches adopted within the scope of enterprise information systems in defense industry organizations. In this context, the study focuses on the points related to use of system implemented as a pilot project in a large defense industry company. The descriptive method was used in the study. Accordingly the, data were gathered by a questionnaire from employees who experienced the product lifecycle management system implemented as a pilot project in the defense industry organization. 164 employees answered the questionnaires and the data obtained from the questionnaires were presented with descriptive statistics and chi-square values. Findings show that more than three quarter of the employees (75.9%) needed to transfer data between the information systems. Additionally, 39% of the employees stated that they easily get used to piloted practices. On the other hand, 35.4% of employees experienced difficulties about accessing to required information and %31.1 had issues related to interface use. 42.9% of the respondents found some inadequacies with the strategy followed for the integration of processes. Despite the faced negative aspects, more than three-quarters of respondents considered the implementation of the system across the company to be useful and very useful. The results reflected that after the implementation of the system in the analysed defence company, the experienced difficulties were mainly related to interface and information retrieval. It was understood that most of the employees thought that there are shortcomings in the strategy followed during the system implementation process. However, a significant number of employees believe that the implemented system has offered positive gains for business processes. In conclusion the study highlights that employees’ experience and feedback should be incorporated into the processes to reduce the difficulties encountered in implementing product lifecycle management systems and to improve the strategies followed.
Keywords: Product lifecycle management; enterprise information systems; implementation process; integrated systems; defense industry